Hepatitis C may enhance key amplifiers of psoriasis. (17th May 2016) - Chun, K.; Afshar, M.; Audish, D.; Kabigting, F.; Paik, A.; Gallo, R.; Hata, T.
Abstract: Background: Multiple studies have noted an association between hepatitis C and psoriasis, but it is not known whether psoriasis is a result of treatment modalities for hepatitis C or a result of hepatitis C alone. Objective: To examine the relationship between psoriasis and hepatitis C by measuring the expression of cathelicidin, TLR9 and IFNγ in psoriatic lesional and non‐lesional skin in HCV‐positive and negative psoriatic patients. Methods: Two 2 mm punch biopsies of lesional and non‐lesional skin in 10 patients who were HCV‐negative psoriatics and seven HCV‐positive psoriatics were used to measure cathelicidin, TLR9 and IFNγ mRNA expression by quantitative reverse‐transcriptase polymerase chain reaction (qRT‐PCR). Results: The mRNA levels of cathelicidin, TLR9 and IFNγ were significantly higher in both non‐lesional and lesional skin of HCV‐positive patients with psoriasis as compared to HCV‐negative psoriatic patients. Additionally, the IFNγ level in lesional skin of HCV‐positive psoriatic patients was higher than the IFNγ level seen in non‐lesional skin of those same patients. Conclusion: These findings suggest that HCV infection upregulates these inflammatory cytokines, possibly increasing susceptibility to developing psoriasis.